Microsurgical Treatment and Follow-Up of KOOS Grade IV Vestibular Schwannoma: Therapeutic Concept and Future Perspective - Won, Sae-Yeon; Kilian, Andreas; Dubinski, Daniel; Gessler, Florian; Dinc, Nazife; Lauer, Monika; Wolff, Robert; Freiman, Thomas; Senft, Christian; Konczalla, Juergen; Forster, Marie-Therese; Seifert, Volker (Frontiers in Oncology, 2020)
Purpose: Surgery of KOOS IV vestibular schwannoma remains challenging regarding the balance of extent of tumor resection (EoR) and functional outcome. Our aim was to evaluate the outcome of surgical resection and define a cut-off value for safe resection with low risk for tumor regrowth of KOOS IV vestibular schwannoma. Methods: All patients presenting at the authors’ institution between 2000 and 2019 with surgically treated KOOS IV vestibular schwannoma were included. Outcome measures included EoR, facial/hearing nerve function, surgical complications and progression of residual tumor during the median follow-up period of 28months. Results: In 58patients, mean tumor volume was 17.1±9.2cm3, and mean EoR of 81.6±16.8% could be achieved. Fifty one patients were available for the follow-up analysis. Growth of residual tumor was observed in 11patients (23.9%) followed by adjuvant treatment with stereotactic radiosurgery or repeat surgery in 15patients (29.4%). Overall serviceable hearing preservation was achieved in 38patients (74.5%) and good facial outcome at discharge was observed in 66.7% of patients, significantly increasing to 82.4% at follow-up. Independent predictors for residual tumor growth was EoR ≤ 87% (OR11.1) with a higher EoR being associated with a very low number of residual tumor progression amounting to 7.1% at follow-up (p=0.008). Conclusions: Subtotal tumor resection is a good therapeutic concept in patients with KOOS IV vestibular schwannoma resulting in a high rate of good hearing and facial nerve function and a very low rate of subsequent tumor progression. The goal of surgery should be to achieve more than 87% of tumor resection to keep residual tumor progression low.